Power, Mobility and the Economic Vulnerability of Borderlands. Issue 3 (3rd July 2017) - Bressan, Giorgia
ABSTRACT: The political boundary between Italy and Yugoslavia, superimposed after the Second World War, extended through lands with a common historical, cultural and economic trajectory. The boundary constituted an ideological divide but the pre-existence of deeply entrenched relations promoted, from the outset, the establishment of a local permeable border. This article explores how, in the context of freedom of movement, borderland residents experience the convenience of border proximity and—by expressing their preference for the foreign market—create major drawbacks for their own domestic economy. Specifically, the low excise duty in Slovenia incentivizes Italian consumers to refuel abroad. How does an open border impact on the dynamics of the fuel market in the high-tax country? Applying the Global Production Network analytical framework, I assess how the attractiveness of the foreign fuel market poses specific challenges both to Italian institutions and economic actors who have vested interests in the local economy. This analysis also reveals how daily international shopping practices are a mass behavior difficult to eliminate. The explicit inclusion of non-corporate actors into the study of the fuel production network offers an important contribution to current understandings of international market outcomes. In fact, the border management policy does not restrict residents' mobility and the redistribution of competencies and functions amidst multiple institutional actors make it difficult to develop a policy able to defend borderland needs.